The Utilization of Ride Sourcing Applications in the UAE: A Structural Equation Model - Elsamahy, Nada Medhat Hassanin Abdelaziz (2023)
A Master of Science thesis in Engineering Systems Management by Nada Medhat Hassanin Abdelaziz Elsamahy entitled, “The Utilization of Ride Sourcing Applications in the UAE: A Structural Equation Model”, submitted in December 2023. Thesis advisor is Dr. Vian Ahmed. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).